Antifatigue Effects of Antrodia cinnamomea Cultured Mycelium via Modulation of Oxidative Stress Signaling in a Mouse Model. (23rd March 2017) - Liu, Yange; Li, Lanzhou; An, Shengshu; Zhang, Yuanzhu; Feng, Shiwei; Zhao, Lu; Teng, Lirong; Wang, Di
Abstract : Antrodia cinnamomea, a folk medicinal mushroom, has numerous biological effects. In this study, we aim to assess whether the antifatigue effects of A. cinnamomea mycelia (AC) and its underlying mechanisms are related to oxidative stress signaling using behavioral mouse models and biochemical indices detection. Mice were orally treated with AC at doses of 0.1, 0.3, and 0.9 g/kg for three weeks. AC had no effect on the spontaneous activities of mice indicating its safety on central nervous system. Furthermore, results obtained from weight-loaded forced swimming test, rotary rod test, and exhausted running test confirmed that AC significantly enhanced exercise tolerance of mice. Biochemical indices levels showed that these effects were closely correlated with inhibiting the depletion of glycogen and adenosine triphosphate stores, regulating oxidative stress-related parameters (superoxide dismutase, glutathione peroxidase, reactive oxygen species, and malondialdehyde) in serum, skeletal muscle, and liver of mice. Moreover, the effects of AC may be related with its regulation on the activations of AMP-activated protein kinase, protein kinase B, and mammalian target of rapamycin in liver and skeletal muscle of mice. Altogether, our data suggest that the antifatigue properties of AC may be one such modulation mechanism via oxidative stress-related signaling in mice.